Effect of Silica Nanoparticles on Quasi-Static Indentation and Impact Properties of Glass Fibre Reinforced Epoxy Polymer Composites - Emi Nor Ain Mohammad, Nurul; Jumahat, Aidah; Arthur, Anthony (International Journal of Engineering and Technology, 2018)
The present study aims to investigate the effect of the silica nanoparticles on the quasi-static indentation and impact properties of glass fiber reinforced polymer (GFRP) composite laminates. The unmodified and modified GFRP composite laminates were fabricated using vacuum bagging method. The epoxy resin was modified with three different silica nanoparticles weight percentages; 5 wt.%, 10 wt.% and 15 wt.%. Quasi static indentation tests were conducted using Instron Universal Testing Machine in accordance to ASTM D7136. Drop weight impact tests were performed using Instron Dynatup 8250 Impact Tester under low energy level (50 J) in accordance to ASTM D6264. The failure mode and damage mechanisms involved during both tests were characterized by observing the indented surfaces and impacted area using an optical microscope. The 15 wt % silica nanoparticle modified GFRP composite laminates showed the highest energy absorb and maximum load when compared to unmodified GFRP composite laminates.Â Â  Â